Penilaian program i-Think di sekolah Wilayah Persekutuan Kuala Lumpur / Shamsazila Sa’aban - Shamsazila , Sa’aban (2018)
The purpose of this study is to evaluate the outcome of the i-THINK program at schools in the Federal Territory of Kuala Lumpur who have been exposed to the faceto-face i-THINK program (pioneer, cohort 1 and cohort 2). Specifically, this study intended to identify the outcome levels of the i-THINK program based on perceptions of 602 teachers and 651 pupils. Before the level of outcome was identified, the evaluation of input and activity levels of i-THINK program was carried out based on the perceptions of 602 teachers, 209 administrators and 108 DRIVE team members. Subsequently, the evaluation of output levels of the i-THINK program is also based on teachers’ perception. In addition, the outcome level between primary and secondary school pupils were compared. The difference in input, activity, output and outcome levels between pioneer, cohort 1 and cohort 2 schools teachers were also identified. Additionally, the contribution of the input component towards activity levels, the contribution of activity components towards output levels, and the contribution of output components towards outcome levels were also identified in this study. i-THINK program evaluation is based on the Logic Model by using cross-sectional survey design. Data were collected by distributing questionnaires and were later on processed by using IBM-SPSS software version 22.0, which involved descriptive statistical methods such as mean and standard deviation as well as inferential statistical methods such as independent sample T-Test, MANOVA and multiple regression. Findings showed that teachers’ outcome level was only moderate for knowledge component vii where the mean score was 3.54, moderate for attitude component (Mean = 3.53), moderate for skill component (Mean = 3.50) and high for aspiration component (Mean = 3.85). Meanwhile, pupils’ outcome levels were identified to be moderate for knowledge component with mean score of 3.61, high for attitude component (Mean = 3.73), moderate for skill component (Mean = 3.20) and high for aspiration component (Mean = 4.14). For the evaluation of the input level, it was found that the overall score based on teachers’ perception was high where the mean score was 3.79. Similarly, the overall scores based on administrators' perception (Mean = 4.07) and DRIVE team members’ perception (Mean = 3.90) were also high. In addition to that, the evaluation of activity level recorded high mean scores based on teachers’ (Mean = 3.90), administrators' (Mean = 4.20), and DRIVE team members’ (Mean = 4.07) perceptions. The evaluation of output level based on teachers’ perception was also found to be high where the mean score was 3.75. The results of independent T-test analysis found that primary and secondary school pupils were from the same variance and there were significant differences in the level of knowledge, attitudes and aspirations between them when the significant level (p) was less than 0.05. Next, this study also found that there were significant differences in input levels and activity levels between pioneer, cohort 1 and cohort 2 school teachers where the significant levels (p) showed less than 0.017 of assigned significant value. However, there was no significant difference in the output and outcome levels of the i-THINK program between teachers at the three categories of school. Multiple regression analysis found that the input components were predictors that contribute 62.3 percent to the variance of the i-THINK program activity level. In addition to that, the activity components were predictors that contribute 26.6 percent to the variance of i-THINK program output level. The output components were predictors that contribute 40.1 percent to the variance of the i- viii THINK program outcome level. The findings of this study provide information to stakeholders to find out the outcome of the i-THINK program and to enable subsequent improvement actions can be presented as a proposal for the i-THINK program to be strengthened and streamlined.